CAR-Treg cell therapies and their future potential in treating ocular autoimmune conditions - Abraham, Alan R.; Maghsoudlou, Panayiotis; Copland, David A.; Nicholson, Lindsay B.; Dick, Andrew D. (Frontiers in Ophthalmology, 2023)
Ophthalmic autoimmune and autoinflammatory conditions cause significant visual morbidity and require complex medical treatment complicated by significant side effects and lack of specificity. Regulatory T cells (Tregs) have key roles in immune homeostasis and in the resolution of immune responses. Polyclonal Treg therapy has shown efficacy in treating autoimmune disease. Genetic engineering approaches to produce antigen-specific Treg therapy has the potential for enhanced treatment responses and fewer systemic side effects. Cell therapy using chimeric antigen receptor modified T cell (CAR-T) therapy, has had significant success in treating haematological malignancies. By modifying Tregs specifically, a CAR-Treg approach has been efficacious in preclinical models of autoimmune conditions leading to current phase 1-2 clinical trials. This review summarises CAR structure and design, Treg cellular biology, developments in CAR-Treg therapies, and discusses future strategies to apply CAR-Treg therapy in the treatment of ophthalmic conditions.